Screening of microorganisms from pineapple waste for fructooligosaccharides production - Tan, L. S.; Mohd Shafiq, Mohd Sueb; Chua, K.; Siti Hajar Noor, Shaarani; Shariza, Jamek (IOP Publishing, 2020)
Fructooligosaccharides (FOS) are one of the well-known low caloric value sweeteners with prebiotic properties that promote positives effects on consumer's health. They are synthetically produced by transfructosylation of sucrose via microbial enzymes which are β-fructofuranosidases (FFase) (EC 3.2.1.26) and fructosyltransferase (FTase) (EC 2.4.1.9). Despite the large number of microbial FTases that are produced, the yield of FOS is low and has poor stability, thus, only a few of them have the potential for industrial application. Research for a new source of microbial enzyme for FOS production becomes necessary due to the high demand for FOS in the pharmaceutical and food industry. Fruit waste such as pineapple waste can be an alternative source of microbial enzyme for FOS production beside can be recycled as FOS substrate. This will reduce the dumping and open burning of these waste which eventually will lead to environmental pollution. This paper presents an experimental study of microbial screening from pineapple waste that can catalyze FOS production. Three different parts of pineapple waste were used in this study which are peels, pulps, and leaves. From screening, all the five isolated bacteria which belong to gram-positive groups did possess both hydrolytic and fructosyltransferase activity with bacteria isolated from leaves showed the highest fructosyltransferase activity which is 0.91 U/ml. Bacterial identification using sequencing of 16S rRNA showed that the isolated bacteria is from the genus Bacillus sp.